Study Results of Darkhan-Uul residents’ Tuberculosis Knowledge,Attitude and Practice - G, Tsendmaa; N, Uyanga; G, Davaa (Caucasus Journal of Health Sciences and Public Health, 2020)
There are 3985 total new incidences of tuberculosis were registered, out of which 55.4% or 2206 cases were registered in Darkhan-Uul.